Fuentes alternativas de materia prima - Spanevello, Rolando Angel (2013)
Biomass is the source of renewable carbon that will allow to achieve the future development of our society. With the prospect of the fossil resources depletion, it is necessary to find new alternative sources of energy and raw materials. Chemistry will play a key role to design new materials from biomass which will reshape our way of living and consumption.